Cicero’s De officiis in Humanist School Instruction – The Philologus Incomparabilis Hieronymus Wolf and His Great Commentary (1563) - Walther Ludwig (Ciceroniana On Line)
Hieronymus Wolf (1516-1580), Rector of the Gymnasium at Augsburg, was one of the most prominent Classicists of the 16th century. Cicero’s De officiis was regarded at Wolf’s time as the best Latin book on moral philosophy. Wolf read that text with his students, commented on it, and published an edition with commentary at Basel 1563. The great commentary differs essentially from the usual philological commentaries: not only does it offer literary and structural explanations, but it also analyzes the morality of Cicero’s statements, and instructs its readers to act accordingly. Thus, it is a revealing document of humanist school instruction. The paper shows this commentary’s context and peculiarities in general, and also by a catalogue of specific examples.